2019
DOI: 10.1523/jneurosci.1120-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of RasGRF2, But Not RasGRF1, Alters Cocaine Reward in Mice

Abstract: Ras/Raf/MEK/ERK (Ras-ERK) signaling has been implicated in the effects of drugs of abuse. Inhibitors of MEK1/2, the kinases upstream of ERK1/2, have been critical in defining the role of the Ras-ERK cascade in drug-dependent alterations in behavioral plasticity, but the Ras family of small GTPases has not been extensively examined in drug-related behaviors. We examined the role of Ras Guanine Nucleotide Releasing Factor 1 (RasGRF1) and 2 (RasGRF2), upstream regulators of the Ras-ERK signaling cascade, on cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
4
9
0
Order By: Relevance
“…We encourage clinicians to research and understand the importance of a molecular framework to explain the current underpinnings of endorphinergic/dopaminergic mechanisms related to opioid deficiency syndrome and a generalized reward processing deficiency [ 19 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Along these same lines, many RDS subtypes have also been linked to hypodopaminergia using sophisticated imaging techniques [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…We encourage clinicians to research and understand the importance of a molecular framework to explain the current underpinnings of endorphinergic/dopaminergic mechanisms related to opioid deficiency syndrome and a generalized reward processing deficiency [ 19 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Along these same lines, many RDS subtypes have also been linked to hypodopaminergia using sophisticated imaging techniques [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ras-ERK pathway is largely known for its regulation of cell proliferation, differentiation, survival, and drug-mediated behaviors. A recent study found that RasGRF2 (RAS protein-specific guanine nucleotide-releasing factor 2) mediates cocaine self-administration (SA) in mice via an ERK-dependent mechanism [ 49 ]. Our study discovered that RasGRF2 was up-regulated after Ang II infusion and could serve as a novel target for Ang II action, and the RasGRF2-Ras-ERK signal axis may play an important role in Ang II-mediated tPVAT pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that cocaine self-administration (SA) was increased in RasGRF2 knock-out (KO) mice relative to their wild-type littermates (WT), which we attributed to a decrease in cocaine reinforcement and compensatory increase in intake to achieve similar putative reward (Bernardi et al, 2019). Importantly, these alterations in cocaine intake were accompanied by an attenuation of the cocaine-induced increase in pERK in the ventral and dorsal striatum in RasGRF2 KO mice.…”
Section: Introductionmentioning
confidence: 93%
“…The extracellular signal-regulated kinases (ERK) cascade (Ras/ Raf/MEK/ERK; Ras-ERK), a member of the mitogen-activated protein kinase (MAPK) family, is an important signaling pathway linking signals from cell surface receptors with changes in gene expression (Grewal et al, 1999;Orton et al, 2005). This pathway has been implicated in the acute and long-term effects of drugs of abuse, including cocaine and other psychostimulants (Valjent et al, 2006;Papale et al, 2016;Bernardi et al, 2019), alcohol (Sanna et al, 2002;Faccidomo et al, 2009;Agoglia et al, 2015;Faccidomo et al, 2015), and nicotine (Brunzell et al, 2003;Valjent et al, 2004;Valjent et al, 2005;Wilar et al, 2019), likely regulating striatal drug-dependent synaptic plasticity (Girault et al, 2007;Cerovic et al, 2013). In terms of nicotine, administration (0.4 mg/kg) in mice has been demonstrated to increase the phosphorylation of ERK1/2 (pERK1/2) in the ventral and dorsal striatum (Valjent et al, 2004;Valjent et al, 2005; but see Brunzell et al, 2003), mesolimbic dopamine structures that have both been shown to mediate neuroadaptations associated with drug dependence (Koob and Volkow, 2010;Lobo and Nestler, 2011).…”
Section: Introductionmentioning
confidence: 99%